Beispiel Nr: 01
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-1/0)\qquad Q(-8/0) \\\\ \\ \textbf{Rechnung:} \\ P(-1/0)\qquad Q(-8/0) \qquad a=-14 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=-14(x+1)(x+8)\\ y=-14(x^2- x \cdot \left(-8\right) +1\cdot x +\left(-1\right)\cdot \left(-8\right) )\\ y=-14(x^2 +9 x+8) \\ y= -14x^2+126x-112 $